Laminar-Turbulent Transition 1995
DOI: 10.1007/978-3-642-79765-1_61
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Boundary-Layer, Sound Receptivity and Control

Abstract: SummaryThe receptivity of a laminar boundary layer on a flat plate is experimentally studied in the presence of 2-D roughness and freestream sound. The work is carried out in the ASU Unsteady Wind Tunnel. It is shown that the T-S wave amplitude can be less than that of the smooth-surface case downstream from the roughness due to a superposition of unstable waves. Thus, receptivity studies of localized sources must consider constructive-destructive interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…On the other hand, the irrotational parts of the freestream disturbances (sound) contribute to the initial amplitudes of the 2-D T-S waves (Kosorygin et al 28 ) Thus, freestream sound and turbulence present a different set of problems in the understanding, prediction, and control of boundary transition and, as such, each require unusual experimental and computational techniques. One needs knowledge, being able to separate the amplitudes, frequencies, length scales, and orientations of both the sound and vorticity components present in the freestream.…”
Section: Why Is Receptivity Important?mentioning
confidence: 99%
“…On the other hand, the irrotational parts of the freestream disturbances (sound) contribute to the initial amplitudes of the 2-D T-S waves (Kosorygin et al 28 ) Thus, freestream sound and turbulence present a different set of problems in the understanding, prediction, and control of boundary transition and, as such, each require unusual experimental and computational techniques. One needs knowledge, being able to separate the amplitudes, frequencies, length scales, and orientations of both the sound and vorticity components present in the freestream.…”
Section: Why Is Receptivity Important?mentioning
confidence: 99%
“…It was found that K s = 0.031. After normalization with C r (α r ) (see above) this gives a receptivity coefficient for the experiments by Kosorygin et al (1995) of G ar = 0.212. Taking again the influence of Reynolds number and frequency parameter into account, which requires an interpolation over a wider range than for the experiment of Saric et al (1991), this value reduces to G ar = 0.161 for the present conditions and becomes rather close to (somewhat higher than) the value of G ar = 0.134 reported here.…”
Section: Comparison With Related Receptivity Experimentsmentioning
confidence: 99%
“…It is necessary to note some important experimental papers devoted to this problem. After the famous work by Aizin & Polyakov (1979) the excitation of the two-dimensional instability waves by acoustics on two-dimensional roughness elements was studied experimentally by Kosorygin, Levchenko & Polyakov (1985), Kosorygin (1986), Saric, Hoos & Kohama (1990), Wiegel & Wlezien (1993), Zhou, Liu & Blackwelder (1994), Kosorygin, Radeztsky & Saric (1995) and others. It was found that the acoustics excite the two-dimensional TS-waves even on a microscopically small non-uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the acoustic disturbances contribute to the initial amplitudes of the two-dimensional Tollmien-Schlichting (T-S) waves [1], whereas the vorticity waves contribute to the three-dimensional behavior of the breakdown process [2,3]. It is believed that the acoustic disturbances contribute to the initial amplitudes of the two-dimensional Tollmien-Schlichting (T-S) waves [1], whereas the vorticity waves contribute to the three-dimensional behavior of the breakdown process [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Boundary layer receptivity is the process by which disturbances in the external free-stream flow or at the wall surface interact with the boundary layer and generate internal waves. It is believed that the acoustic disturbances contribute to the initial amplitudes of the two-dimensional Tollmien-Schlichting (T-S) waves [1], whereas the vorticity waves contribute to the three-dimensional behavior of the breakdown process [2,3]. It is now known that the receptivity of boundary layers to free-stream turbulence or to surface imperfections plays an important role in the prediction of the transition onset.…”
Section: Introductionmentioning
confidence: 99%